Resurgence Following Higher or Lower Quality Alternative Reinforcement - Shahan, Timothy A; Sutton, Gabrielle M; Van Allsburg, Jack; Avellaneda, Matias; Greer, Brian D (Journal of the experimental analysis of behavior, 2024)
Resurgence is a temporary increase in a previously suppressed target behavior following a worsening in reinforcement conditions. Previous studies have examined how higher rates or magnitudes of alternative reinforcement affect suppression of the target behavior and subsequent resurgence. However, there has been no investigation of the effects of higher versus lower qualities of alternative reinforcement on resurgence. Using a three-phase resurgence preparation with rats, the present experiments examined the effects of an alternative reinforcer that was of higher (Experiment 1) or lower (Experiment 2) quality than the reinforcer that had previously maintained the target behavior. The results of both experiments showed greater reductions in target behavior with a higher quality alternative reinforcer and larger increases in target responding when a higher quality alternative reinforcer was removed. Along with prior findings with higher rates and magnitudes of alternative reinforcement, these findings suggest that variations in reinforcer dimensions that increase the efficacy of alternative reinforcement also tend to increase resurgence when alternative reinforcement is removed. The results are discussed in terms of the resurgence as choice in context model and in terms of potential clinical implications.